A synthetic chalcone derivative, 2-hydroxy-3′, 5, 5′-trimethoxychalcone (DK-139), suppresses the TNFα-induced invasive capability of MDA-MB-231 human breast cancer cells by inhibiting NF-κB-mediated GROα expression. Issue 1 (1st January 2016) - Lee, Da Young; Lee, Da Hyun; Jung, Jung You; Koh, Dongsoo; Kim, Geum-Soog; Ahn, Young-Sup; Lee, Young Han; Lim, Yoongho; Shin, Soon Young
Graphical abstract: Abstract: 2-Hydroxy-3′, 5, 5′-trimenthoxyochalcone (DK-139) is a synthetic chalcone-derived compound. This study evaluated the biological activity of DK-139 on the inhibition of tumor metastasis. Growth-regulated oncogene-alpha (GROα) plays an important role in the progression of tumor development by stimulating angiogenesis and metastasis. In this study, DK-139 inhibited tumor necrosis factor alpha (TNFα)-induced GROα gene promoter activity by inhibiting of IκB kinase (IKK) in MDA-MB231 cells. In addition, DK-139 prevented the TNFα-induced cell migration, F-actin formation, and invasive capability of MDA-MB-231 cells. These findings suggest that DK-139 is a potential drug candidate for the inhibition of tumor cell locomotion and invasion via the suppression of NF-κB-mediated GROα expression.